Eksistensi Tradisi Adat dalam Perspektif Hukum Islam : Studi Tradisi Nikah Batin Adat Buton di Samarinda - Ahmad Rijalul Akbar; Rahmat Fadillah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The Nikah Batin tradition of the Buton community in Sidodadi, Samarinda, is a customary pre-wedding procession symbolizing the spiritual union of the prospective bride and groom. This study is an empirical legal research with an anthropological law approach, aiming to examine its implementation procedures and analyze it from the perspective of Islamic law. Data were collected through interviews with traditional leaders and tradition practitioners, then qualitatively analyzed using Islamic marriage theory, the concept of 'urf, Islamic legal maxims, and the Receptie a Contrario theory. The findings reveal that the stages of the tradition (escort by sara, presentation of kakumbu, joint recitation of the shahadah, and joining of hands) are rich in the values of cultural preservation and the strengthening of marital sacredness. However, the Islamic legal review categorizes this practice as 'urf fāsid due to pre-marital physical interaction and inconsistencies with the pillars and valid conditions of a marriage contract. In conclusion, the implementation of this tradition needs to be aligned with Sharia principles so that its noble customary values remain preserved without violating the provisions of Islamic law.